AXIAL-SYMMETRIC FIELDS IN THE FRAMEWORK OF EJNSTEIN THEORY - Abazyan, H. H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2006)
The method of approximate determination of parameters of stationary axial-symmetric fields of rotating configurations at the third and the forth approximation of angular velocity is proposed.
Keywords: method of approximate determination; stationary axial-symmetric fields; angular velocity